Posouzení informačního systému firmy a návrh změn - Kozina, Josef (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Diplomová práce je zaměřená na společnost Carbide s.r.o., která podniká v oboru výroby a ostření speciálních nástrojů. Hlavní náplní práce je návrh zlepšení aktuálního stavu informačního systému. Práce je rozdělena do tří částí, kdy první část seznamuje čtenáře s teorií dané problematiky, druhá část se zabývá analýzou nynějšího stavu a poslední třetí část tvoří vlastní návrhy pro zlepšení aktuální situace s informačním systémem.

The diploma thesis is focused on the company Carbide s.r.o., which is engaged in the production and sharpening of special tools. The main focus of the thesis is the proposal to improve the current state of the information system. The thesis is divided into three parts, where the first part introduces the reader to the theory of the issue, the second part deals with the analysis of the current situation and the last third part consists of the actual proposals for improving the current situation with the information system.
Information System Assessment and Proposal of ICT Modification
Keywords: Informační systém; bezpečnost; efektivita; SWOT analýza; ZEFIS; Information system; security; efficiency; SWOT analysis; ZEFIS